Parameterized analysis and crossing minimization problems - Zehavi, Meirav (Computer science review, 2022)
In this survey/introductory article, we first present the basics of the field of Parameterized Complexity, made accessible to readers without background on the subject. Afterwards, we survey some central questions in Graph Drawing that concern the analysis of crossing minimization problems from the viewpoint of parameterized analysis, as well as put forward some of the remaining challenges. This article originated from an invited talk given at the 29th International Symposium on Graph Drawing and Network Visualization.